SIMBOR LIMBOR REPRESENTASI MUSIK TERHADAP MITOLOGI SIMBOR LIMBOR - Zulianda, Reza; Mering, Aloysius; Munir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of the creation of this work is to revitalize the Simbor Limbor Mythology which is the old culture of the Sungai Limau village community. the idea of the creation of this work is: the representative form of music over Simbor Limbor Mythology by using the Malay music idiom. The steps used in the creation of this work are: preparation, incubation, illumination and verification with transferen and syncretic approaches. The information used in the creation of this work is the result of direct observation and interviews with informants from the villagers of Sungai Limau. Based on these results the authors describe the subject matter in each Movement made.Keywords : Simbor Limbor Mythology, Sungai Limau, Music Representation.